Application of new aerated concrete slag material on roofs: a preliminary study. (April 2015) - Dai, S. B.; Zhang, Y. C.; Huang, J.; Peng, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, an aerated concrete slag material was first applied on roofs, and the transient heat transfer of improved thermal insulation roof was simulated using ANSYS. Moreover, the thermal insulation performance of roof was evaluated. Meanwhile, PBECA was used to calculate the energy consumption of building. Research shows the relationship between the maximum value of inner surface temperature fluctuation and the thickness of the insulation layer in Wuhan, Changsha and Nanjing is: y = −0.0148x + 1.9649, y = −0.0202x + 2.6809, y = −0.0181x + 2.3994, respectively. After optimisation of roof, the energy consumption of top room is reduced by 8.0%, and the material cost is reduced by 36.9%.